2013
DOI: 10.3414/me12-01-0096
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping Sensor Network System for Automatic Vital Signs Collection

Abstract: This paper proposed a clinical sensor network system that relieves nurses from vital signs input tasks. The result clearly shows that the proposed system increases the efficiency and safety of the nursing process both subjectively and objectively. It is a step toward new generation of point of nursing care systems where sensors take over the tasks of data input from the nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Reduced working time was reported by one study on an automated system for collecting vital signs and symptoms (Kuroda et al, 2013). The authors found that using Bluetooth access points for thermometer and blood pressure meters in a 22-bed dialysis unit halved the time nurses spent using hospital information systems.…”
Section: Using Robots For Patient Monitoringmentioning
confidence: 98%
See 1 more Smart Citation
“…Reduced working time was reported by one study on an automated system for collecting vital signs and symptoms (Kuroda et al, 2013). The authors found that using Bluetooth access points for thermometer and blood pressure meters in a 22-bed dialysis unit halved the time nurses spent using hospital information systems.…”
Section: Using Robots For Patient Monitoringmentioning
confidence: 98%
“…Another study on bar code-assisted system found that the direct transmission of data reduced measurement errors to 1.3% during the evaluation period and that the prototype correctly identified patients was 87.4% of cases (Kuroda et al, 2013). Three studies looked at measurement errors in automated devices for detecting falls and monitoring urine output.…”
Section: Using Robots For Patient Monitoringmentioning
confidence: 99%
“…Most of the studies aim at some kind of behaviour analysis -mostly to detect or prevent specific risks [125][126][127][128][129][130][131] or to analyse behaviour patterns to support care decisions. [132][133][134] Other application fields are vital sign monitoring, [135][136][137][138] external risk detection 139 and tracking or identification of persons. 140,141 The most common application of sensors in this review is the analysis of behaviour for the prevention of falls.…”
Section: Monitoring/sensorsmentioning
confidence: 99%
“…M=( N, L, F, S, Z) is generally used: the state list N is a finite state set; the input event list L is the set of all received events in the system; the state shift function F defines the state transition logic; the initial state S is a special state of the system; and the termination state is a sub-set of N [7][8][9].…”
Section: Fsm-based Active Tracking Modelmentioning
confidence: 99%